2018
DOI: 10.1002/joc.5448
|View full text |Cite
|
Sign up to set email alerts
|

The seasons’ length in 21st century CMIP5 projections over the eastern Mediterranean

Abstract: The eastern Mediterranean (EM) is expected to be influenced by climate changes that will significantly affect ecosystems, human health and socio‐economic aspects. One aspect of climate change in this vulnerable area is the length of the seasons, especially that of the rainy winter season against the warm and dry summer. Here, the synoptic seasons’ definition of Alpert, Osetinsky, Ziv, and Shafir (2004a) was applied to an ensemble of eight Coupled Model Inter‐Comparison Project phase 5 (CMIP5) models, under RCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 85 publications
(124 reference statements)
5
58
1
Order By: Relevance
“…Due to the absence of 12UTC data at the 1,000‐hPa level in CMIP5 models, we use U and V wind components and temperature from the 850‐hPa level, as well as sea level pressure (SLP). The compatibility between the 1,000 and the 850‐hPa levels, and that of the 12UTC with daily classifications was examined by Hochman et al (, c) and Berkovic (), respectively, and was shown to fit well. Nevertheless, the ability of the two downscaling methods used, that is, the modified algorithm for the synoptic classification (the “weather regimes”) and the “analogues” to downscale observed seasonal precipitation is evaluated here for both the NCEP/NCAR reanalysis and the CMIP5 models.…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…Due to the absence of 12UTC data at the 1,000‐hPa level in CMIP5 models, we use U and V wind components and temperature from the 850‐hPa level, as well as sea level pressure (SLP). The compatibility between the 1,000 and the 850‐hPa levels, and that of the 12UTC with daily classifications was examined by Hochman et al (, c) and Berkovic (), respectively, and was shown to fit well. Nevertheless, the ability of the two downscaling methods used, that is, the modified algorithm for the synoptic classification (the “weather regimes”) and the “analogues” to downscale observed seasonal precipitation is evaluated here for both the NCEP/NCAR reanalysis and the CMIP5 models.…”
Section: Methodssupporting
confidence: 90%
“…Modeled data for six models participating in the fifth phase of the Coupled Model Inter‐Comparison Project (CMIP5; Taylor et al, ) were retrieved from the World Data Center for Climate (WDCC‐DKRZ, http://cera-www.dkrz.de/WDCC/ui/Index.jsp) data portal. These models were previously utilized in Hochman et al (, c, and 2019) (list of models see Table ) and their ability to simulate annual and extreme precipitation indices over the eastern Mediterranean was previously presented by Samuels et al (). Furthermore, these models' ability to simulate the annual cycle of the prevailing eastern Mediterranean synoptic systems, their frequencies, and dynamics for the historical period were presented in Hochman et al (, c, and 2019).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A limited global analysis across realms suggested that animals from more 15 stable environments have greater capacity for acclimation compared to unstable ones, 16 but pointed out that generality of such patterns is limited because much of the world is 17 undersampled (Seebacher et al, 2015). 18 On the rapidly warming Israeli coast, which is the southeastern edge of distribution of 19 most Mediterranean and Atlanto-Mediterranean species, and where the water is 20 naturally hottest in the basin, tidepool ecology has not been studied before, but it is 21 assumed that the pools can get extremely hot when disconnected from the sea. This 22 study focuses on the small rockpool shrimp Palaemon elegans (Rathke 1837).…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal acclimatization of oxygen consumption rates has been previously documented valuable feature that may lead to adaptive shifts in thermal breadth, thermal optima and 20 higher fitness (Somero, 2002). Acclimatization is a known mechanism that enables the 21 organism to cope with the changing environmental temperature that occurs seasonally.…”
mentioning
confidence: 99%